An Assessment of the Effectiveness of Online Training among Trainees in an IT Firm in Nagpur City - Dr. Sushant Waghmare, Ms. Nisha Bar (Drugs and Cell Therapies in Hematology, 2021)
The following study was aimed at analysing the effectiveness of online training programmes during COVID-19 pandemic. A survey was conducted of Trainees in an IT Firm in Nagpur City. Online training has become the essential training methodology during the pandemic. It is effective, safe and can cater to the needs of the employees. At the same time, it is also not very personal, certain communication barriers exist in online training. A survey was conducted using a structured questionnaire for the trainees. A total of 34 respondents replied with completed questionnaires. Simple random sampling methodology was implemented while conducting this study. The findings suggest that online training is effective among the employees and it caters to their personal and growth needs. The training proved to be majorly effective in teaching the employees about navigating the platform easily and the training material proved to be sufficient. It must also be noted that perhaps since the sample belonged to the IT Sector, the uptake of technical means of training and materials was far more easily adopted by the trainees. Further studies should focus on trainees from different sectors as well.